КОНКУРЕНТОСПОСОБНОСТЬ КАК ФАКТОР И СТРАТЕГИЧЕСКИЙ ОРИЕНТИР РАЗВИТИЯ НЕФТЯНОЙ ОТРАСЛИ - Абилдаев, О С (Journal of Economic Research & Business Administration, 2015)
Theoretical bases of competitiveness of oil branch of Kazakhstan are opened. As the economic category a competition carries out a number of functions of regulation, motivation, distribution and the control. The basic precondition of competitiveness - manufacture and realization of the competitive goods. Presence of competitiveness in branch grows out merges of the most succeeding companies. If to follow M. Portera's theory in Kazakhstan are inherent a competition on the basis of factors of manufacture and development of a competition on the basis of investments.